INVESTIGATION OF HOT DEFORMATION AND DUCTILITY BEHAVIOR OF AISI H10 STEEL - M. Kamali Ardakani (Isfahan University of Technology, 2021)
The aim of this study was to investigate the behavior of hot deformation and occurrence of restoration phenomena during the deformation of AISI H10 hot work tool steel. For this purpose, hot tensile test was performed on the steel in the temperature range of 900-1150 ºC with a temperature interval of 50 ºC and at a constant strain rate of 0.1s-1. The microstructures were examined and the curves of hot flow and ductility were drawn. According to the curves and microstructures, ductility was lower at temperatures of 900 ºC and 950 ºC due to inactivity of repair processes and the presence of carbides. Ductility increased in the temperature range of 1000-1100 ºC due to the occurrence of dynamic recrystallization. Finally, ductility decreased in the temperature of 1150 ºC due to the dissolution of carbide particles and grain growth. The results obtained from hot tensile test and microstructural studies at a constant strain rate of 0.1s-1 revealed that the appropriate temperature range for deformation of AISI H10 hot work tool steel was 1000-1100 ºC.